Wpływ akceptacji choroby na zachowania zdrowotne pacjentów z marskością wątroby = The impact of the acceptance of the disease on the health behaviors of patients with liver cirrhosis - Krzyżanowska, Ewa; Matej, Agnieszka; Łuczyk, Robert; Kropornicka, Beata; Baczewska, Bożena; Olszak, Cecylia; Nowicka, Elżbieta; Daniluk, Jadwiga (Journal of Education, Health and Sport, 2017)
Krzyżanowska Ewa, Matej Agnieszka, Łuczyk Robert, Kropornicka Beata, Baczewska Bożena, Olszak Cecylia, Nowicka Elżbieta, Daniluk Jadwiga. Wpływ akceptacji choroby na zachowania zdrowotne pacjentów z marskością wątroby = The impact of the acceptance of the disease on the health behaviors of patients with liver cirrhosis. Journal of Education, Health and Sport. 2016;6(11):225-244. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.166302 http://ojs.ukw.edu.pl/index.php/johs/article/view/3990 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 22.10.2016. Revised 30.10.2016. Accepted: 11.11.2016. Wpływ akceptacji choroby na zachowania zdrowotne pacjentów z marskością wątroby The impact of the acceptance of the disease on the health behaviors of patients with liver cirrhosis Ewa Krzyżanowska1, Agnieszka Matej2, Robert Łuczyk1, Beata Kropornicka1, Bożena Baczewska1, Cecylia Olszak1, Elżbieta Nowicka1, Jadwiga Daniluk1 1 Katedra Interny z Zakładem Pielęgniarstwa Internistycznego Wydział Nauk o Zdrowiu Uniwersytetu Medycznego w Lublinie 2 Absolwentka Wydziału Nauk o Zdrowiu Uniwersytetu Medycznego w Lublinie Streszczenie Cel pracy. Celem pracy było określenie wpływu akceptacji choroby na zachowania zdrowotne pacjentów z marskością wątroby. Materiał i metoda. Badaniami objęto grupę 100 chorych z rozpoznaną marskością wątroby. Badania zostały przeprowadzone od kwietnia do czerwca 2016 r. w Oddziale Wewnętrznym Gastrologicznym w I Wojskowym Szpitalu Klinicznym oraz w Klinice Gastroenterologii Samodzielnego Publicznego Szpitala Klinicznego nr 4 w Lublinie. W pracy wykorzystano Skalę Akceptacji Choroby (AIS) oraz Inwentarz Zachowań Zdrowotnych Zygfryda Juczyńskiego (IZZ). Wyniki badań. Z badań wynika, że 69% ankietowanych prezentuje średni poziom akceptacji choroby natomiast wysoki cechuje tylko 12% ankietowanych.19% badanych nie akceptuje choroby. Większy poziom akceptacji choroby występował w grupie kobiet niż mężczyzn oraz w grupie badanych mieszkających w mieście. Jednak różnice w ocenie nie były statystycznie istotne. Najwyższe nasilenie zachowań zdrowotnych odnotowano w kategorii zachowań profilaktycznych, najniższe w kategorii prawidłowych nawyków żywieniowych. Różnice w ocenie również nie były statystycznie istotne. Wnioski. Stwierdzono, że kobiety w większym stopniu niż mężczyźni akceptują swoją chorobę. Czas trwania choroby wpływa na jej akceptację, badani z najkrótszym stażem chorowania łatwiej akceptują chorobę niż badani chorujący dłużej niż 2-3 lata. Zachowania zdrowotne badanych nie są zależne od miejsca ich zamieszkania, jednak wyższy wskaźnik zachowań zdrowotnych obserwuje się u badanych mieszkających w mieście. W badanej grupie wykształcenie determinuje prawidłowe zachowania zdrowotne, im wyższe wykształcenie badanych tym większe nasilenie prawidłowych zachowań zdrowotnych. Czas trwania choroby nie ma wpływu na zachowania zdrowotne pacjentów marskością wątroby, jednak najwyższe nasilenie zachowań zdrowotnych prezentują badani chorujący najkrócej a najniższe chorujący dłużej niż dwa lata. Słowa kluczowe: akceptacja choroby, zachowania zdrowotne, marskość wątroby Summary Aim of the study. The aim of the study was to determine the effect of the acceptance of the disease on the health behavior of patients with cirrhosis of the liver. Material and methods. The study involved a group of 100 patients diagnosed with cirrhosis of the liver. The study was conducted from April to June 2016. in the Department of Internal Gastroenterology in the Military Clinical Hospital and the Department of Gastroenterology of the Independent Public Clinical Hospital No. 4 in Lublin. The study used Acceptance of Illness Scale (AIS) and the Behavioral Health Inventory Siegfried Juczyński (IZZ). Findings. Research shows that 69% of respondents presented average level of acceptance of the disease is characterized by high while only 12% ankietowanych.19% of respondents did not accept the disease. A greater level of acceptance of the disease occurred in women than men and in the group of respondents living in the city. However, the differences in rating were not statistically significant. The highest intensity of health behaviors was recorded in the category of prevention, the lowest in the category of normal eating habits. Differences in ratings were also not statistically significant. Conclusions. It was found that women more than men accept their illness. The duration of the disease affects its acceptance, the subjects with the shortest experience of illness easier to accept the disease than subjects who have developed more than 2-3 years. Health behaviors surveyed are not dependent on their place of residence, but a higher rate of health behaviors observed in subjects living in the city. In the group of education determines the proper health behavior, the higher the education the greater the severity of the respondents correct health behaviors. The duration of the disease does not affect the health behavior of patients cirrhosis of the liver, but the highest severity of health behaviors present subjects who have developed the shortest and lowest sick more than two years. Keywords: acceptance of illness, health behaviors, cirrhosis of the liver